Choirs in end-of-life care: a thematic literature review. (2nd August 2022) - Ryan, Colleen; McAllister, Margaret; Mulvogue, Jennifer
Abstract : Background: Choirs are an important source of wellbeing for people experiencing palliative and end-of-life care. Threshold choirs are an innovation that could be more widely introduced, as hospital and palliative care settings have become more open to community input. Aims: Before such choirs are recommended and encouraged, evidence for their effectiveness and implementation barriers need to be known. Methods: A literature review was undertaken in 2019 and 2020 using CINAHL, PUBMED, Medline, ProQuest, Google Scholar and an internet manual search. Findings: The review identified a total of 26 research and discussion papers relevant to the topic of choir in palliative care settings. Conclusion: Following the review, guidelines were developed that may be useful to assist choirs and service providers to effectively introduce this valuable initiative. Choirs may be a creative, and uplifting arts-based activity to augment and enrich the culture of person-centred care during palliative care processes.